2012
DOI: 10.1186/1743-8977-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene expression and cytokine production by crystalline vs. amorphous silica in human lung epithelial cells

Abstract: BackgroundExposure to respirable crystalline silica particles, as opposed to amorphous silica, is associated with lung inflammation, pulmonary fibrosis (silicosis), and potentially with lung cancer. We used Affymetrix/GeneSifter microarray analysis to determine whether gene expression profiles differed in a human bronchial epithelial cell line (BEAS 2B) exposed to cristobalite vs. amorphous silica particles at non-toxic and equal surface areas (75 and 150 × 106μm2/cm2). Bio-Plex analysis was also used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 70 publications
8
52
0
2
Order By: Relevance
“…Our study and recent reports in the literature demonstrate that gene expression profiling in human lung epithelial cells can be an important tool for analyzing the pathogenicity of potentially harmful fibres and particles (42)(43)(44). Gene expression profiling, for example in response to asbestos, is valuable to define early molecular effects as demonstrated in diverse human cells, such as normal human bronchial epithelial cells (NHEC) (45), human lung adenocarcinoma cells (A549) (46,47), SV40-transformed human bronchial epithelial cells (BEAS-2B) and SV40-immortalized pleural mesothelial cells (MET5A) (47).…”
Section: Discussionsupporting
confidence: 64%
“…Our study and recent reports in the literature demonstrate that gene expression profiling in human lung epithelial cells can be an important tool for analyzing the pathogenicity of potentially harmful fibres and particles (42)(43)(44). Gene expression profiling, for example in response to asbestos, is valuable to define early molecular effects as demonstrated in diverse human cells, such as normal human bronchial epithelial cells (NHEC) (45), human lung adenocarcinoma cells (A549) (46,47), SV40-transformed human bronchial epithelial cells (BEAS-2B) and SV40-immortalized pleural mesothelial cells (MET5A) (47).…”
Section: Discussionsupporting
confidence: 64%
“…These results are consistent with those found in the literature for silica and other NPs [4,35,36]. Perkins et al previously compared crystalline and amorphous silica NPs, but found that only cristobalite upregulated IL6 and IL8 in lung BEAS-2B cells whereas amorphous silica NPs only modulated CCL5 (RANTES) expression [4].…”
Section: Inflammation and Nonspecific Response (Level 2)supporting
confidence: 91%
“…This discrepancy between our data and previously published data illustrates the possible heterogeneity of the results in the NP literature, probably directly linked to the different nature of the NPs. In particular, fumed AERO-SIL® 200 NPs differ from the amorphous silica NPs of the previous study [4], with a surface area 100 times greater. The "TREM1 signaling pathway" was triggered, leading to proinflammatory immune responses.…”
Section: Inflammation and Nonspecific Response (Level 2)mentioning
confidence: 52%
See 1 more Smart Citation
“…Silica dust can also increase the mortality rate from respiratory diseases and cardiovascular diseases (3). Exposure to silica can cause abnormal gene expression (4). Regulation of gene expression not only depends on genetic mechanism, also with epigenetics mechanisms without genetic coding change, including DNA methylation and histone acetylation and so on (5).…”
Section: Introductionmentioning
confidence: 99%